USE OF NEOLOGISMS IN ECONOMIC TERMS - Yuldasheva Dilnoza Bekmurodovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes new words and expressions, namely neologisms, that appeared in the economic sphere. The article includes the main meanings of new words and expressions that appeared in the economic sphere, their application to the economic sphere, scope and explanation. Information is provided on how new words and expressions are located in economic terminology and how they are used.